Prevalence of low weight and small for gestational age in Argentina: Comparison between the INTERGROWTH-21st standard and an Argentine reference - Revollo, Gabriela Beatriz (2017)
Introduction. The term “low birth weight” (< 2500 g) encompasses preterm newborns and term newborns small for gestational age (SGA) (< P10). The World Health Organization defines low weight (LW) as a birth weight < P3 of weight/ age. There is no consensus at an international level about which standards and/or references related to birth weight for gestational age (GA) should be used to assess SGA and LW among preterm newborns. LW and SGA prevalence was determined using the INTERGROWTH21st standard and Urquía’s reference for the Argentine population, and agreement between the prevalence observed with both tools was analyzed. Population and methods. Observational, analytical, and retrospective study based on all births occurred in 2013 as reported by the Argentine National Ministry of Health. Exclusion criteria were GA < 24+0 - > 42+6 weeks, twin pregnancy, and missing data on weight, GA, and sex. Prevalence was estimated by sex, region, and prematurity category for LW and SGA according to the standard and the reference. Agreement was assessed using the Kappa index. Results. The prevalence of LW and SGA was higher according to the standard among preterm newborns; the contrary was observed among fullterm newborns. Statistical significance varied based on GA category, sex, and region. A higher prevalence was observed in the northern regions of Argentina, and agreement among prevalence values ranged from weak to very good. Conclusions. Prevalence agreement of LW and SGA observed according to the standard and the reference among preterm and full-term newborn infants was moderate, with interregional variability. Results propose new auxological perspectives in the epidemiological assessment of intrauterine growth restriction in Argentina.